Phytomyza trolliicaulis (Diptera Agromyzidae) a new species miner ofTrollius europaeus L. (Ranuncolaceae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Phytomyza trolliicaulis, a new species of Agromyzidae, stem miner of Trollius europaeus, is described. The male genitalia place trolliicaulis in the "opaca" group, living on Ranuncolaceae plants.
Keywords: Agromyzidae; Phytomyza trolliicaulis; Trollius europaeus